Making things happen : community participation and disaster reconstruction in Pakistan - Thomas, Jane Murphy (Catastrophes in Context ;, 2022)
"Drawing on the Pakistan Earthquake Reconstruction and Recovery Project (PERRP), this volume explores the sociocultural side of post-disaster infrastructure reconstruction. As the latter is often fraught with delays and even abandonment-one cause being ineffective interactions between construction and local people-PERRP used anthropological and participatory approaches. Along with strong construction management, such approaches led to the rebuilding being completed on time. As disasters are increasing in number and intensity, so too will be the need for reconstruction, for which PERRP has lessons to offer"--